Synthesis and Characterisation of Mg2+ and Al3+ Co-Doped CoCr2O4 Inorganic Pigments With High Near-Infrared Reflectance - Wei, Xueling; Zou, Xiangyu; Deng, Zhifeng; Bao, Weiwei; Ai, Taotao; Zhang, Qi (Frontiers in Materials, 2022)
A new class of near-infrared (NIR) reflectance pigments based on Co1−xMgxCr2−yAlyO4 (x = 0–1 and y = 0–2) was synthesised using the Pechini-type sol-gel process. The developed powders were characterised by thermogravimetry and differential scanning calorimetry, X-ray diffraction (XRD), ultraviolet–visible near-infrared diffuse reflectance spectroscopy, and colour Commission Internationale del'Eclairage (CIE) 1976 (L*a*b*) colour scales. The XRD patterns revealed characteristic peaks of the spinel structure with good crystallinity. Substituting Mg2+ for Co2+ ions in the tetrahedral positions and Al3+ for Cr3+ ions in the octahedral positions of CoCr2O4 reduces the cost and changes the colour of the pigment (green to yellow and then blue). Moreover, the synthesised pigments exhibited high NIR solar reflectance in the 780–2,500 nm wavelength range. The thermal and chemical stability of the pigments was also studied. Our findings demonstrate the potential for applying these pigments in cool colourants.